2017
DOI: 10.1097/npt.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2 Years of Exercise on Gait Impairment in People With Parkinson Disease: The PRET-PD Randomized Trial

Abstract: Background and Purpose This study presents a secondary analysis from the Progressive Resistance Exercise Training in Parkinson disease (PRET-PD) trial investigating the effects of progressive resistance exercise (PRE) and a PD-specific multimodal exercise program, modified Fitness Counts (mFC), on spatial, temporal, and stability-related gait impairments in people with Parkinson disease (PD). Methods Forty-eight people with PD were randomized to participate in PRE or mFC 2×/week for 24 months; 38 completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 44 publications
0
36
1
16
Order By: Relevance
“…Patients with PD have a decrement of stride length which may be attributed to a decreased sagittal inclination angle [37]. In patients with PD, ankle PF is associated with gait velocity and stride length [38]. ese articles all suggested that kinematic parameters had an impact on spatiotemporal gait parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PD have a decrement of stride length which may be attributed to a decreased sagittal inclination angle [37]. In patients with PD, ankle PF is associated with gait velocity and stride length [38]. ese articles all suggested that kinematic parameters had an impact on spatiotemporal gait parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Este fato pode ser atribuído as especificidades do TM, principalmente devido aos exercícios de força, que auxiliam no recrutamento de unidades motoras, trazem benefícios ao equilíbrio corporal e redução da rigidez muscular, de forma a melhorar parâmetros da marcha e contribuir na prevenção de quedas [35,36]. [20] reforça a hipótese de que intervenções multimodais contribuem para melhora da velocidade da marcha, assim como melhora das variáveis espaciais e/ou temporais da marcha de indivíduos com DP [20].…”
Section: Análise Estatísticaunclassified
“…Nossos resultados vão de encontro ao estudo de [20], que após intervenção com um programa de exercícios multimodais a curto prazo (<6 meses), houve melhora nos parâmetros espaciais e temporais da marcha a exemplo a velocidade da marcha.…”
Section: Análise Estatísticaunclassified
See 2 more Smart Citations